PowerShell Core for Linux Administrators Cookbook : Use PowerShell Core 6.x on Linux to automate complex, repetitive, and time-consuming tasks /: Use PowerShell Core 6.x on Linux to automate complex, repetitive, and time-consuming tasks. (2018) - Jayaram, Prashanth; Iyer, Ram
No abstract available